ANALISIS KECEPATAN PUTARAN HOTPLATE MAGNETIC STIRRER BERBASIS ARDUINO UNO - Dabukke, Hotromasari; Primasyukra, Mhd. Aldi; Lasiyah, Nani; Gaol, Midun Andrike Lumban (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2023)
The Arduino Uno Based Hotplate Magnetic Stirrer Rotational Speed ​​Design has been successfully carried out. The function is to stir and heat one solution with another solution which aims to make a homogeneous solution with the help of a Magnetic stir bar (Stir Bar). The purpose of this design is to know the design of the HotPlate Magnetic Stirrer with 400 Rpm Rotation Speed ​​Settings and to determine the accuracy of the Hotplate Magnetic Stirr rotation speed. The method used is the experimental method. The components in this design are Arduino uno and consist of DC Stepper motor components, motor drivers, 20x4 lcd. The working principle of the design of the hotplate magnetic stirrer based on Arduino Uno. The PLN AC 220V current enters the power supply which converts to a DC voltage of 12V 10A, then Arduino Uno receives a DC voltage of 12V to turn on circuits such as motor drivers that require 12V voltage directly from the power supply, 9V stepper motors, 5V buzzers. Furthermore, the stepper motor will run according to the command set on keyped. To compare the rotational speed settings, use the tachometer calibration tool. The test results show the Rotational Speed ​​of the Arduino Uno-Based Hotpate Magnetic Stirrer, the rpm rotation speed is in accordance with the settings and the results obtained are 10% tolerance. The results of measuring the voltage on the power supply.